Managing Islam In Singapore: A Strong And Resilient State - Saat, Norshahril (Studia Islamika, 2022)
The Malay-Muslim community makes up about 13.4 per cent of the 5.6 million Singapore population. The relationship between the community and the state has been amicable, although there were instances of tension. Since the 1970s, it has undergone what observers portray as an Islamic resurgence. Drawing from Fukuyama’s state capacity paradigm, the Singapore state, led by the People’s Action Party (PAP) government, can be considered a strong state. The notion of ‘strong’ here does not necessarily mean illiberal or authoritarian state—as political observers represent it to be—but can also mean ‘effective’. This article examines Singapore’s effectiveness in managing state-Malay community relations particularly on issues of security and religiosity. It argues that the state’s strength does not derive from the use of hard power or legislations, but from its flexibility and deep knowledge of when, what and how to intervene. It concludes with a discourse on how the state deals with challenges to its strength in more recent political science framework about weakening the state or the end of power.